A novel association between Rhodnius neglectus and the Livistona australis palm tree in an urban center foreshadowing the risk of Chagas disease transmission by vectorial invasions in Monte Alto City, Sao Paulo, Brazil - Carvalho, Danila B. [UNESP]; Almeida, Carlos E. [UNESP]; Rocha, Claudia S. [UNESP]; Gardim, Sueli [UNESP]; Mendonca, Vagner J. [UNESP]; Ribeiro, Aline R.; Alves, Zulimar C. P. V. T.; Ruellas, Kellem T.; Vedoveli, Alan; Rosa, João Aristeu da [UNESP] (Elsevier B.V., 2014)
After several public notifications of domiciliary invasions, palm trees were investigated in downtown Monte Alto City, Sao Paulo State, Brazil, in proximity to the city hall building, the main church, condominiums and marketing establishments. One hundred seventy four palm trees of 10 species were investigated, in which 72 specimens of Rhodnius neglectus, a potential Chagas disease vector, were captured via manual methods. All insects were collected from dead leaves, organic debris and bird nests in the only three Livistona australis palm trees in the central park square. This was the first record of R. neglectus colonizing this palm species. Although no Trypanosoma cruzi was found by abdominal compression followed by light microscopy, the poor nutritional status of the bugs hampered the examination of gut contents for parasite detection. Furthermore, the central crowns of the trees, which shelter bats (Chiroptera: Mammalia), could not be carefully searched for insects due to difficult access. This new finding highlights the sudden alteration in insect behavior, probably as a result of man's interference. This report aims to warn those involved in the health system about this new threat, justifying detailed research of the area to evaluate the magnitude of this emerging public health issue. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Triatomines; Domiciliation; Antropogenic changes; Vector behavior